Descriptions of larvae of Megadytes (Coleoptera: Dytiscidae: Dytiscinae): The hypothesis of monophyletic origin revisited - Michat, Mariano Cruz (2006)
The three larval instars of Megadytes (Paramegadytes) glaucus (Brullé, 1838) and the third-instar larvae of M. (Bifurcitus) magnus Trémouilles & Bachmann, 1980 and M. (Trifurcitus) robustus (Aubé, 1838) are described and illustrated for the first time, with particular emphasis on the morphometry and chaetotaxy. A key to the subgenera of Megadytes Sharp, 1882 is presented. In a cladistic analysis of third-instar larval characters, Megadytes is resolved as non-monophyletic; the species of Cybistrini studied, except those included in the subgenus Trifurcitus Brinck, 1945, share three synapomorphies: (i) medial projection of frontoclypeus truncate apically, with many apical setae directed forwards; (ii) lateral projections of frontoclypeus project forwards, not flattened; and (iii) median process of prementum rounded apically. The clade composed of the subgenera Megadytes s. str., Paramegadytes Trémouilles & Bachmann, 1980 and Bifurcitus Brinck, 1945 along with Cybister lateralimarginalis (De Geer, 1774) is well supported by three synapomorphies: (i) head capsule subrectangular and (ii) distal third of mandible more strongly projected inwards, (iii) with a ring of long, hair-like setae. The two species of the subgenus Paramegadytes have bilobed lateral projections on the frontoclypeus. Megadytes (M.) marginithorax (Perty, 1830) is characterized by the very narrow notches between the medial and lateral projections of frontoclypeus. No synapomorphies were discovered to group together the two species of the subgenus Bifurcitus.